2000
DOI: 10.1021/jp0004056
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Atomic and Molecular Hydrogen Elimination from Small Alkanes Following 157-nm Excitation

Abstract: Photodissociation of a series of C 3 -C 9 alkanes following 157 nm excitation has been investigated using the photofragment translational spectroscopy (PTS) technique. Three series of alkanes, normal alkanes, branched alkanes, and cyclic alkanes, were studied and the atomic hydrogen (H) and molecular hydrogen (H 2 ) elimination from their photodissociation were experimentally investigated. Experimental results show that the dynamics of the H and H 2 elimination processes from larger n-alkanes is quite similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Recently, we have studied the ionization/dissociation processes of some alkyl iodides by means of time-of-flight (TOF) mass spectrometry under strong (∼10 16 W cm −2 ) femtosecond [8] and picosecond [9,10] laser irradiation. In both cases, an intense ionic signal corresponding to atomic and molecular hydrogen ions has been recorded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have studied the ionization/dissociation processes of some alkyl iodides by means of time-of-flight (TOF) mass spectrometry under strong (∼10 16 W cm −2 ) femtosecond [8] and picosecond [9,10] laser irradiation. In both cases, an intense ionic signal corresponding to atomic and molecular hydrogen ions has been recorded.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen atoms are produced mostly by a C H bond rupture from the terminal carbon atoms of the alkyl chain. On the other hand, other groups [14][15][16] have shown that for the case of small alkanes the vast majority of the released molecular hydrogen is formed from hydrogen atoms bonded to carbons in the middle of the alkyl chain. Molecular hydrogen formation from the other hydrogen atoms of the skeleton (i.e., from the terminal CH 3 groups) is also possible and it is found that they are released with higher kinetic energies (∼3.3 eV) compared to those generated from the middle of the alkyl chain (∼1.5 eV).…”
Section: Introductionmentioning
confidence: 99%
“…The absorption spectra and retention volumes of the peaks labeled "M" and "D" in the GPC chromatograms in Figures 1 and 2 are consistent with their structural assignments as mono-and di-heneicosylpyrenes. In addition to generating large concentrations of heneicosyl radicals at various positions along the alkane chain (via C-H bond cleavage), MeV range X-rays can cleave C-C bonds, creating shortened chains terminated with radical centers (Wu et al 2000). Each radical type can add (preferentially) to the 1-position of pyrene (Mitchell et al 1979), yielding an alkylpyrene after loss of a hydrogen atom (Lapouyade et al 1986).…”
Section: Resultsmentioning
confidence: 99%
“…The atomic and molecular hydrogen eliminations from ethylene have more kinetic energy releases than that from propene. 15 The H 2 /H ratio increases from 2.1 to 5.6 ͑from 0.16 to 1.6͒ as the number of carbon atoms in normal ͑cyclic͒ alkane increases from 3 to 8, which is contrary to the trend of H 2 /H ratios from ethylene to propene. 28 The preliminary results indicate that only the leading part of the H atom correlates to C 2 H 3 and the rest is due to a 2H elimination.…”
Section: G Comparison With Ethylene and Cyclopropanementioning
confidence: 87%
“…15,16 Four distinct dissociation pathways for the atomic hydrogen elimination, molecular hydrogen elimination, C 2 H 4 ϩCH 2 formation, and C 2 H 3 ϩCH 3 formation have been identified, and their branching ratios have also been roughly estimated to be 0.14, 0.01, 0.68, and 0.17, respectively. Recently, the photodissociation dynamics of cyclopropane at 157.6 nm has been investigated in our laboratory.…”
Section: Shown Inmentioning
confidence: 99%